Cloud Point Extraction for Separation and Microamounts Determination of Copper (II) and Cobalt (II) - Shawket. K.Jawad; Shatha. S.Tarish (Al-Qadisiyah Journal of Pure Science, 2017)
Copper(II) and Cobalt(II) preconcentrated and separated in different samples after complexation by 2-[4-Nitro phenylazo]-4,5-diphenyl imidazole (NPADPI) was presented with cloud point extraction method, are quantitatively extracted in TritonX-100 following separation. 5ml of ethanol was added to surfactant-rich phase prior to its analysis by UV-Vis spectrophotometry, All experimented conditions limited such as pH, concentration of TritonX-100, temperature, time of heating, stoichiometry for complex extracted ,as well as applications about determination quantity of Copper(II)and Cobalt(II) in different samples.